Empowering BUSECO: linking sweetpotato seed producers across Eastern Uganda for growth and sustainability - Namazzi, S.; Rajendran, S.; Omongo, C.; Namanda, S.; Yada, B. (2025)
This case study documents the institutional strengthening and market development journey of the Busoga Commercial Seed Producers and Marketing Cooperative (BUSECO) in Kamuli District, Eastern Uganda. With support from the International Potato Center (CIP), NaCRRI, MAAIF, and local partners, BUSECO was officially registered as a seed-producing entity and secured a UGX 50 million (USD 13,888) loan from Pride Microfinance. Between 2022 and 2025, the cooperative increased its seed sales by 54%, expanded its variety portfolio from 2 to 8 sweetpotato varieties, and established partnerships with Iowa State University and Andree Food International. The cooperative also adopted digital management tools such as the Business Investment Decision (BID) and Seed Requirement Estimation (SRE) tools to improve decision-making. Key lessons include the importance of inclusive leadership, savings revitalization, and diversified income streams. BUSECO now serves as a model for sustainable, market-oriented farmer cooperatives in Uganda’s vegetatively propagated crop seed systems.